Cicero im Klassenzimmer. Eine österreichische Fallstudie - Cicero in the Classroom. An Austrian Case Study - Schreiner, Sonja (Ciceroniana On Line, 2020)
The article explores how Cicero’s role in the Austrian curriculum changed and developed over the past decades, examining the various approved editions for use in schools (as an area of tension between educational policy and specialised study) and offering a critique of how Latin as a subject shifted from a linguistic and literary framework to one determined by cultural studies – a shift that the article analyses in terms of its advantages and disadvantages, as well as pitfalls and uncertainties.